A Mixed Methods Study| Teacher Perceptions of the Impact of Implementation of Response to Intervention at the High School Level - Fontenot, Amy R. (University of Louisiana at Lafayette, 2016)
The ultimate goal of elementary and secondary education is to produce citizens who can contribute to and succeed in today’s global economy (Alliance for Excellent Education, 2011; Biancarosa & Snow, 2006). The most significant skill required in reaching that level of success and contribution is a person’s ability to read. “Where the press is free, and every man able to read, all is safe” (Jefferson, 1816, para. 5). Approximately 200 years later, where are America’s literacy rates? Sixty-eight percent of eighth grade students read below level (NAEP, 2009). The overarching goal of this research study was to develop best practices for RTI implementation at the high school level that include teacher professional learning, effective universal components, and methods that contribute to increased student performance, specifically in the areas of literacy development and reading comprehension. The purpose of this study was to (1) examine the programs and processes teachers are using to identify, intervene, and remediate reading deficits with ninth grade students; (2) review and analyze data from ninth grade below-benchmark; (3) review and analyze progress data of students receiving interventions; and (4) explore teachers’ perceptions regarding resources, professional learning, and student performance. For this research study, both quantitative and qualitative methods were used. The study reported descriptive statistics of student performance on the universal screening measure at five high schools. The qualitative component of this study was designed to collect data using focus group interviews with 33 teacher participants. The information gained from the focus group interviews with teachers was crucial to determining what impact the components of RTI have on student performance. Findings indicated a need for additional remediation resources, increased professional development, technical assistance and support with the scheduling and staffing components of RTI, as well early identification of students needing to participate in the RTI process.